2011
DOI: 10.1111/j.1432-2277.2011.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein S deficiency in a living liver donor

Abstract: Summary Protein S deficiency is a thrombophilia associated with increased risk of thromboembolic episodes in affected patients. Traditionally, protein S deficiency in a potential donor was considered an absolute contraindication to living donor liver transplantation, both due to the increased risk incurred by the thrombophilic donor as well as the risk of transmitting the thrombophilia to the liver recipient, as protein S is predominantly produced by the liver. We present the first successful case of living do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Nine potential donors with hypercoagulability risks were excluded in our series. Six cases were related to a low level of protein S or protein C. Kitchens et al reported a successful LT with a graft from a donor with low protein S level . Preservation of normal protein S level in the recipient and the intermediate deficiency state (>40%) were thought to be the reason of this success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine potential donors with hypercoagulability risks were excluded in our series. Six cases were related to a low level of protein S or protein C. Kitchens et al reported a successful LT with a graft from a donor with low protein S level . Preservation of normal protein S level in the recipient and the intermediate deficiency state (>40%) were thought to be the reason of this success.…”
Section: Discussionmentioning
confidence: 99%
“…Six cases were related to a low level of protein S or protein C. Kitchens et al reported a successful LT with a graft from a donor with low protein S level. (29) Preservation of normal protein S level in the recipient and the intermediate deficiency state (>40%) were thought to be the reason of this success. They applied a strict protocol with venous thromboembolism prophylaxis and administration of 4 units of daily fresh frozen plasma until postoperative day 5.…”
Section: Discussionmentioning
confidence: 99%
“…As complex and unpredictable in onset and severity, a few risk factors for venous thromboembolism after liver transplantation were identified, for example, prolonged immobilization, administration of excessive procoagulant factors, and peripherally inserted central catheter lines [14,15]. Other factors involved defects in the proteins that normally regulated anticoagulation, such as protein C, protein S, and antithrombin deficiency, transmitted from donors to recipients [29][30][31][32], and this can be missed Similarly, kidney and heart transplant recipients have been reported to be at risk of venous thromboembolism as mentioned previously [16,18,[33][34][35]. In heart transplant recipients, Elboudwarej et al [19] even demonstrated that lower extremity DVT posed a high risk of pulmonary embolism and death despite use of thromboprophylactic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…As complex and unpredictable in onset and severity, a few risk factors for venous thromboembolism after liver transplantation were identified, for example, prolonged immobilization, administration of excessive procoagulant factors, and peripherally inserted central catheter lines . Other factors involved defects in the proteins that normally regulated anticoagulation, such as protein C, protein S, and antithrombin deficiency, transmitted from donors to recipients , and this can be missed preoperatively if donors were not screened for thrombophilic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The potential reason for a non-thrombotic phenotype in the latter report could be the compensation by extra-hepatic protein S production in the recipient. 42 This underscores the difficulty of thrombophilia screening, especially in the context of live liver donation.…”
Section: 13mentioning
confidence: 99%